Acid‐Responsive Dual‐Targeted Nanoparticles Encapsulated Aspirin Rescue the Immune Activation and Phenotype in Autism Spectrum Disorder. Issue 14 (13th March 2022) - He, Xueqin; Xie, Jiang; Zhang, Jing; Wang, Xiaorong; Jia, Xufeng; Yin, Heng; Qiu, Zhongqing; Yang, Zhihang; Chen, Jiao; Ji, Zhiliang; Yu, Wenqi; Chen, Meiwan; et al.
Abstract: The treatment of autism spectrum disorder (ASD) is one of the most difficult challenges in neurodevelopmental diseases, because of the unclear pathogenesis research and low brain‐lesion targeting efficiency. Besides, maternal immune activation has been reported as the most mature and widely used model of ASD and aspirin‐triggered lipoxin A4 is a potent anti‐inflammatory mediator being involved in the resolution of neuroinflammation in ASD. Therefore, an aspirin encapsulated cascade drug delivery system (Asp@TMNPs) is established, which can successively target the blood–brain barrier (BBB) and microglial cells and response to the acid microenvironment in lysosome. As a result, the mitochondrial oxidative stress, DNA damage, and inflammation of microglial cells are prominently alleviated. After the treatment of Asp@TMNPs, the social interaction, stereotype behavior, and anxious condition of ASD mice are notably improved and the activation of microglial cells is inhibited. Overall, this system successively penetrates the BBB and targets microglial cells, therefore, it significantly enhances the intracephalic drug accumulation and improves anti‐neuroinflammatory efficacy of aspirin, providing a promising strategy for ASD treatment. Abstract : An aspirin encapsulated cascade drug delivery system (Asp@TMNPs) is proposed to rescue the immune activation and phenotype in autism spectrum disorder (ASD). In this system, Asp@TMNPs successively penetrate the blood–brain barrier and target microglial cells, and then significantly enhance the intracephalic drug accumulation and improve anti‐neuroinflammatory efficacy of aspirin, providing a promising strategy for ASD treatment.